How Students’ Self-Efficacy Can Affect Their Mathematical Critical Thinking Ability? - Suhartini, Tutin; Hendriana, Heris; Putra, Harry Dwi (IKIP Siliwangi, 2025)
Critical thinking is an essential skill that students must possess in order to face various academic challenges and the dynamic development of scientific knowledge. Among psychological factors, self-efficacy plays a significant role in students' mathematical critical thinking skills, enabling them to solve tasks or problems in specific situations. This study aims to examine the influence of self-efficacy on students’ mathematical critical thinking abilities. The research employed a quantitative approach with a correlational design to analyze and explore in depth how self-efficacy affects students’ mathematical critical thinking skills. The sample consisted of 25 students from SDN Harapan Mulya. Data analysis was conducted using simple linear regression to determine the extent to which students’ self-efficacy influences their mathematical critical thinking abilities. The results showed a positive and significant influence between self-efficacy and critical thinking skills (p < 0.05), with a coefficient of determination of 0.224. This indicates that students’ self-efficacy contributes 22.4% to the variation in their mathematical critical thinking abilities. Therefore, the conclusion of this study is that the higher the students’ self-efficacy, the higher their mathematical critical thinking skills, which means that self-efficacy significantly influences students’ mathematical critical thinking. These findings highlight the importance of strengthening self-efficacy through various learning approaches to enhance students’ mathematical critical thinking skills.